Analisis Makna Konotasi dalam Lirik Lagu Bertaut Karya Nadin Amizah - Sari, Itika Purnama; Febriyanti, Fira; Ujung, Triana Ayuningsih; Barus, Frinawaty Lestarina (UNIB Press, 2021)
The purpose of this study was to describe the connotative meaning contained in the song Bertaut by Nadin Amizah. The method used in this study is a qualitative descriptive method with the research subject, namely the song Bertaut by Nadin Amizah. The data collection technique used was observation and listening to the song Bertaut by Nadin Amizah. The data analysis technique that has been carried out is by collecting and analyzing the meaning of each sentence contained in the verse of the song Bertaut by Nadin Amizah. The results showed that the connotative meaning in the lyrics of the song Bertaut by Nadin Amizah has an implied meaning, namely the inner bond and very close affection between mother and child until death separates them. The song Bertaut by Nadin Amizah also has positive connotations, such as the words mother, hedgehog, swimming, heartbeat, and so on. In this song also has a negative connotation meaning, namely the word bastard and barking.